(Re)dignification of the human person entitled to the benefit of continued provision provided for in the Federal Constitution of 1988 (Research, Society and Development, 2022)
This work aims to demonstrate how the Continued Benefit, as a right of social assistance, promotes to the elderly and the hyposufficient disabled their economic autonomy and social empowerment, through the guarantee of minimum conditions of existence. Still, it is discussed how social citizenship is only achieved when elementary needs are removed from the lives of the elderly and people with disabilities. To understand the theme, it starts with the concept of human dignity as a value that is born from philosophical and religious discussions and enters the legal world after the second world war, starting to have legal value. By adopting the quali-quanti method and using primary data, issues related to human dignity in the Brazilian case are analyzed and their implications for public policies to promote social assistance, especially in compliance with the provisions of item V of Article 203 of the Constitution Federal. In view of this approach, it is inferred that the Continued Benefit program, managed by the National Social Security Institute (INSS) contributes to meeting one of the Sustainable Development Goals, number 10, as it provides the minimum income to the beneficiaries, reducing inequalities.